TINJAUAN HUKUM PIDANA TERHADAP PUTUSAN HAKIM DALAM PERKARA TINDAK PIDANA PENCURIAN YANG DILAKUKAN OLEH ANAK SECARA BERSAMA- SAMA ( Studi Kasus Putusan Nomor 1927/Pid.Sus.Anak/2020/PN Mks ) - Muh Aufa Aqzani; Ma'ruf Hafidz; Baharuddin Badaru (Qawanin Jurnal Ilmu Hukum, 2020)
Children are the next generation of the nation. Therefore, every child should get his right to play, learn and socialize. But the situation will turn around if children commit crimes together. Law Number 11 of 2012 concerning Child Criminal Justice System. This SPPA Law is a substitute for Law Number 3 of 1997 concerning Juvenile Courts. The Juvenile Court Law is considered to beno longer in accordance with legal needs in the community and has not comprehensively provided special protection to children who are faced with the law. From this background, the problem will be discussed, (1) is Detentionof children in a case decisions number: 1927/Pid.Sus.Anak/2020/PN Mks, has fulfilled the Child Criminal Justice System? And (2) what are the judges' considerations in criminal imposing acts on whom children commit crimes together? This study uses normative legal research methods, uses a statutory approach and a conceptual approach, and examines the primary legal material and secondary legal material. The results of this study indicate that (1) Knowing the legal provisions for the detention of children, according to the juvenile justice system in case decisions number: 1927/Pid.Sus.Anak/2020/PN Mks (2) Knowing the judge's consideration in criminal imposing acts on whom the children commit crimes together?